A Technology-Based Self-Monitoring Intervention for Secondary Students with High-Incidence Disabilities. Issue 3 (September 2021) - Kumm, Skip; Talbott, Elizabeth; Jolivette, Kristine
Secondary students with high incidence disabilities who also display disruptive behaviors struggle to be successful in general education settings. As a result, general education teachers are looking for ways to utilize technology to provide them with opportunities to implement evidence-based interventions in their classrooms. In this study, teachers used MoBeGo, an iPad application, in a single-case withdrawal design (ABAB), to implement self-monitoring in high school general education classrooms with four students who received special education services for a high incidence disability. The results of this study indicate that teachers could implement MoBeGo with fidelity to improve students' academic engagement and appropriate behavior. Additionally, both the teachers and students rated MoBeGo as a socially valid intervention. Implications for practice and future research are discussed.